The role of neutrophil-to-high-density lipoprotein cholesterol ratio in gestational hypertension and preeclampsia: A retrospective cross-sectional study - Bulu, Aykut; Bulu, Gulay (Lippincott Williams & Wilkins, 2025)
This study aimed to assess neutrophil-to-high-density lipoprotein cholesterol ratio (NHR) and other inflammatory and biochemical parameters as potential biomarkers for predicting gestational hypertension (GH) and preeclampsia (PE) in pregnant women. A total of 180 pregnant women were enrolled and divided into 3 groups: 58 with GH, 42 with PE, and 80 normotensive controls. Clinical, demographic, and laboratory data (inflammatory markers, lipid profiles, liver enzyme levels, and kidney function) were also collected. NHR and other biomarkers such as C-reactive protein (CRP) and white blood cell counts were compared across the groups. Statistical analyses, including univariate and multivariate regression, were conducted to identify significant predictors of GH and PE. The NHR was significantly higher in the GH (4.5 +/- 1.1) and PE (5.2 +/- 1.2) groups than in the normotensive controls (3.6 +/- 1.1, P < .001). Inflammatory markers, such as CRP, white blood cell count, and monocyte levels, were elevated in the GH and PE groups. In addition, the levels of glucose, creatinine, and liver enzymes were notably higher in the PE group. The NHR demonstrated a positive correlation with CRP levels. Regression analysis revealed that the NHR (P < .001), CRP (P = .002), and platelet count (P < .001) were independent predictors of GH and PE. The NHR may serve as an early inflammatory biomarker for predicting GH and PE. This finding suggests that NHR, along with other biomarkers, could be incorporated into clinical practice to improve the early identification and management of hypertensive disorders during pregnancy. Further prospective studies are needed to confirm these results and evaluate their clinical utility.
Keywords: CRP; gestational hypertension; neuthrophil to HDL cholesterol ratio; NHR; preeclampsia